Strengthening Students' Interpersonal Communication through Peer Interaction at MI Nurul Iman - Risma Renata; Sarifah, Iva; Yunus, Mahmud (JESS (Journal of Educational Social Studies), 2025)
This study explores the role of peers in strengthening the interpersonal communication skills of 4th grade students at MI Nurul Iman. Interpersonal communication is a fundamental skill that enables children to express ideas, understand others, and engage in effective social interactions. This research employs a descriptive qualitative method involving 32 students and one homeroom teacher as participants. Data were collected through interviews and non-participant observation, analyzed using the Miles and Huberman model which includes data reduction, data display, and conclusion drawing. To ensure data reliability, the study applied data source and method triangulation. Research findings indicate that peers play an important role in strengthening interpersonal communication skills by providing support, feedback, interaction facilities, and behavioral models. Peer interactions also improve students' ability to convey messages, listen actively, empathize, communicate non-verbally, and build self-confidence. These skills are reinforced through students' daily communication contexts at school, such as group discussions, breaks, and seating arrangements among peers. The study highlights the strategic importance of leveraging peer dynamics to foster students' interpersonal communication and provides practical insights for educators to design socially interactive learning environments.